Analisis Pengaruh Store Atmosphere, Harga Dan Produk Terhadap Loyalitas Konsumen Rumah Makan Berkonsep Angkringan (Studi Pada Waroeng Kroepoek Solo) - Senja Silvia, Miranda; , Soepatini, S.E., M.Si., Ph.D (2017)
This study to analyze the influence of store atmosphere, prices and products on consumer loyalty restaurant concept angkringan (studies on waroeng kroepoek Solo). This study also aims to analyze the possibility of variable store atmosphere, price, and product into a model that is able to explain consumer loyalty significantly. The population in this study is all consumers waroeng kroepoek Solo, with the number of samples of 100 respondents. More specifically the sampling technique used is purposive sampling technique, the respondents selected in this study should have been at least twice visited and make purchases on waroeng kroepoek Solo. The types and sources of data used in this study are primary data. Techniques of collecting research data through questionnaires with Likert scale. Data analysis technique used test instrument, validity test, reliability test, and multiple linear regression analysis (t test, F test, and R² test). This research yields several findings. The first is the store atmosphere has a significant effect on the loyaliat consumer of the restaurant concept of angkringan especially on Waroeng Kroepoek Solo. The second finding is that prices have a significant effect on the loyaliat of the consumers of the restaurant especially in Waroeng Kroepoek Solo concept. The third is the product does not have a significant effect on the loyaliat consumer of the restaurant concept of angkringan especially on Waroeng Kroepoek Solo. The latter states that store atmosphere, price, and product are able to significantly explain consumer loyalty variables in Waroeng Kroepoek Solo.